Cytokinin signaling coordinates development of diverse organs in Marchantia polymorpha. (2nd November 2019) - Aki, Shiori S.; Nishihama, Ryuichi; Kohchi, Takayuki; Umeda, Masaaki
ABSTRACT: Cytokinins play an essential role in plant growth and development. A recent study showed that the cytokinin signaling pathway was conserved in the liverwort Marchantia polymorpha, and that it controlled gemma cup and rhizoid formation during thallus development. Here we show that the type-B response regulator, MpRRB, is mainly localized in the nucleus. Moreover, observations of thalli revealed that the distribution of air pores and the shape of the thallus margin are impaired in cytokinin-deficient lines and those defective in cytokinin signaling. This suggests that cytokinins regulate cell division and/or differentiation of precursor cells derived from the apical cell, thereby coordinating development of various organs produced on the thallus.